Sufisme Pedesaan dan Nalar Beragama Inklusif: Ekspresi Keagamaan Majelis Dzikir Birrul Walidain di Karanganyar Jawa Tengah - Mibtadin Mibtadin; Zainal Habib; Mustolehudin Mustolehudin (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This research focuses on how the community in Karangwuni Village Karangmojo Tasikmadu, Karanganyar Regency expresses religious movements as an effort to build a moderate society. Majelis Dzikir and Shalawat Birrul Walidain in the village are very strategic public spaces to instill an inclusive Islamic character. Village communities are synonymous with harmonious behavior and mutual help, and from a diversity perspective, they tend to be open or moderate. This study uses the sociology of religion approach with qualitative methods. This study found that makes taklim in the village became a medium for spiritual empowerment as well as a space for culture. Besides that, the Birrul Walidain taklim assembly is also a public space that displays moderate Islam in the countryside. This study offers the need for a moderate socio-religious movement carried out massively throughout the villages in the archipelago to build a tolerant Islam by prioritizing the principles of tawassuth, tawazun, and tasamuh, to create a peaceful and harmonious society. The existence of an inclusive taklim assembly can be a social capital in building a moderate society.